Gestão do Conhecimento em Bibliotecas Universitárias Públicas: Um estudo sobre o Sistema de Bibliotecas da Universidade Federal do Rio de Janeiro (SIBI/UFRJ) - Souza, Claudia Barbosa dos Santos de (2022)
The Federal University of Rio de Janeiro (UFRJ) is a centenary institution of excellence, considered one of the best universities in Brazil, which has 172 undergraduate courses and distance learning courses, 200 latu-senso specialization courses, and 224 stricto-sensu graduate programs, some of them of international standard. It has 44 libraries that have the objective of interacting with the University's educational and administrative policies. These information units are managed by the coordination of the Library and Information System (SIBI). University libraries are considered to be knowledge organizations, their mission being to support teaching, research and extension activities, endorsing the institutional mission. To manage such demands, especially through remote activities, it is necessary that the management of the library system has the habit of sharing information, and it is necessary that there is a management practice focused on sharing information and knowledge, so that the work performed by all information units is efficient and effective. The networks and systems of university libraries are organizations that have affinities, goals and activities in common. In this context, this research had as object of study the Sistema de Bibliotecas e Informação da Universidade Federal do Rio de Janeiro (SIBI/UFRJ), which has 44 information units located in different campuses. In view of such reality, it was sought to understand: how can knowledge management practices contribute to optimize the management of SIBI/UFRJ? It aimed to analyze the KM practices adopted by SIBI/UFRJ from the perspective of the network society. The specific objectives were: to describe the information and knowledge sharing practices used by SIBI/UFRJ; to present the possible innovative practices in UFRJ libraries that were enhanced due to the absence of face-to-face work; to propose guidelines for implementing KM as possible management practices for UFRJ libraries. This is a quali-quantitative research, of basic purpose, explanatory investigation to be carried out through theoretical and observational research. The research was motivated by the need to understand the factors that influence the management of a public university library system. It was evidenced that the coordination of UFRJ libraries, through SIBI, uses several KM practices in order to enhance its management, acting strategically to manage: people, processes, resources, information, knowledge and everything that needs to be managed, always being aware of the importance of taking care of its most precious capital, the intellectual capital, through strategic management.